Human Anatomy and Physiology Preparatory Course - Liachovitzky, Carlos (Open textbook library., 2015)
The goal of this preparatory textbook is to give students a chance to become familiar with some terms and some basic concepts they will find later on in the Anatomy and Physiology course, especially during the first few weeks of the course. Organization and functioning of the human organism are generally presented starting from the simplest building blocks, and then moving into levels of increasing complexity. This textbook follows the same presentation. It begins introducing the concept of homeostasis, then covers the chemical level, and later on a basic introduction to cellular level, organ level, and organ system level. This second edition incorporates a module on protein synthesis, and a complementary base pairing learning objective as requested by many students. This edition incorporates links to audios for all learning objectives, and many learning objectives have online videos associated to them. The textbook is organized in five Units, divided into sixteen Modules covering a total of fifty-three Learning Objectives. Each learning objective includes a short self-assessment at the end of it.